The origin of superhardness of nanocomposite coatings: analysis of nanoindentation and scratch tests - Lu, Chunsheng; Mai, Y.; Shen, Y. (Springer, 2007)
Nanocomposite coatings characterized by superhardness exhibit unique microstructures and deformation mechanisms at the nanometre scale. Based on the studies of nano-indentation size effect, we show that dislocation-based deformation is gradually replaced by grain-boundary mediated deformation as the hardness of coatings increases, especially for coatings approaching superhardness. The measured hardness of a superhard coating exponentially increases with the decrease of indentation depth, and its intrinsic hardness can be exactly determined by the analysis of indentation size effect. The optimal conditions extracted from acoustic emission signals from scratching superhard nanocomposite coatings are in good agreement with nanoindentation and drilling tests. In the optimal regime, it is the competition between different deformation mechanisms that results in the origin of superhardness in self-organized microstructures of nanocomposite coatings.